Unveiling the patterns and trends in 40 years of global trade in CITES-listed wildlife. (July 2018) - Harfoot, Michael; Glaser, Satu A.M.; Tittensor, Derek P.; Britten, Gregory L.; McLardy, Claire; Malsch, Kelly; Burgess, Neil D.
Abstract: Wildlife trade can provide commercial incentives to conserve biodiversity but, if unsustainable, can also pose a threat. CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) aims to ensure international trade in CITES-listed species is sustainable, legal and traceable. However, large-scale temporal and spatial patterns in wildlife trade are poorly known. We address this by analysing the CITES Trade Database: >16 million shipment records for 28, 282 species, from 1975 and 2014. Over this period, the volume of reported trade in CITES-listed wildlife quadrupled, from 25 million whole-organism equivalents per year to 100 million, and the ratio of wild- to captive-sourced trade in mammals, birds, reptiles, invertebrates and plants declined by an order of magnitude or more. Our findings start to reveal the scale of the legal wildlife trade, shifting trade routes and sources over time and we describe testable hypotheses for the causes of these changes.